Bifunctional Zn2+-solvation structure electrolyte for highly reversible zinc anodes - Wang, Shuai (2024)
Aqueous zinc batteries exhibit promises for energy storage systems because of their attractive advantages including low cost and high safety. However, Zn anodes often face challenges such as water-induced side reactions and dendritic growth. Here, we present an electrolyte engineering with bifunctional Zn2+-solvation structures to solve these problems. 1) The coordination between anions and Zn2+ neutralizes the Zn2+-solvation structure, creating an electrostatic shielding effect that hinders dendritic growth on the Zn surface. 2) The original H-bond networks between water molecules are replaced by the abundant O-H∙∙∙Cl- H-bond networks through the electrostatic confinement, thus capable of reducing the water activity. Moreover, the electrolyte endows the Zn anode with fast plating/stripping behaviors owing to its enhanced ionic migration kinetics. Consequently, the Zn‖Zn cell maintains a high Coulombic efficiency (99.6 %) after 600 cycles. The assembled Zn‖PANI hybrid capacitor exhibits improved electrochemical reversibility and cycling stability over 2000 cycles. This work offers valuable insights into the development of electrolyte design strategies for advanced aqueous energy-storage devices.